2019
DOI: 10.1039/c9tc01182j
|View full text |Cite
|
Sign up to set email alerts
|

A photolithographic stretchable transparent electrode for an all-solution-processed fully transparent conformal organic transistor array

Abstract: A photolithographic stretchable transparent electrode comprising PEDOT:PSS and SWCNT was developed for an all-solution-processed transparent conformal organic transistor array.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 38 publications
0
46
0
Order By: Relevance
“…It has been reported that the mobility of OTFT fabricated with vacuum evaporated gold contacts on a monolayer OSC film was two orders of magnitude lower than those of OTFTs fabricated with 2-or 3-molecular layers of OSC. To overcome this issue, development of a transfer or lamination process for contact electrodes, in which OSC layers are not exposed to the damage during vacuum evaporation, is a key challenge [30][31][32][33][34] . In the previous work 32 , the lamination technique has been demonstrated, where pre-patterned electrodes embedded into an elastic and flexible film, polydimethylsiloxane (PDMS), were employed.…”
mentioning
confidence: 99%
“…It has been reported that the mobility of OTFT fabricated with vacuum evaporated gold contacts on a monolayer OSC film was two orders of magnitude lower than those of OTFTs fabricated with 2-or 3-molecular layers of OSC. To overcome this issue, development of a transfer or lamination process for contact electrodes, in which OSC layers are not exposed to the damage during vacuum evaporation, is a key challenge [30][31][32][33][34] . In the previous work 32 , the lamination technique has been demonstrated, where pre-patterned electrodes embedded into an elastic and flexible film, polydimethylsiloxane (PDMS), were employed.…”
mentioning
confidence: 99%
“…[88] In addition, Cui et al developed a new type of PEDOT:PSS/SWCNT stretchable transparent electrode through one-step photolithography and dry etching (Figure 8a). [103] PEDOT:PSS layers provided good interfacial wettability for SWCNT dispersion, thus forming an ultrathin and uniform conductive film (Figure 8b,c). As a result, this kind of photolithographic PEDOT:PSS/SWCNT electrodes exhibited stretchability of 100% and sheet resistance of 90 Ω sq −1 .…”
Section: Carbon Materials For Stretchable Electrodesmentioning
confidence: 99%
“…Poly(3,4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) semiconducting polymer is solution processable and transparent, having great potential in flexible optoelectronics. [ 88 ] In 2017, Kostianovskii et al. used patterned PEDOT:PSS films as source‐drain electrodes for ambipolar OFETs.…”
Section: Strategies For Reducing Rc In Ofetsmentioning
confidence: 99%